A Study on Mapping the Potential of Rice Production in Banggai Regency - Rumangkang, Olivia Esther Caroline; Effendy, Effendy; Antara, Made; Rauf, Rustam Abd.; Christoporus, Christoporus (AGROLAND The Agricultural Sciences Journal (e-Journal), 2025)
The background of this research is the need to improve regional food security amidst conditions where land degradation, land use changes, and reduced labor can disrupt the proper exploitation of agricultural resources. This study aims to analyze the potential of rice as a food crop in Banggai Regency, Central Sulawesi, which is focusing on the harvested area, production, productivity, and production base by sub-district. Research data were collected from the Central Statistics Agency (BPS, 2024) and the Food Crops, Horticulture, and Plantation Service of Banggai Regency. The analytical approach uses descriptive statistics to describe the harvested area, production, and productivity of rice, and the Location Quotient (LQ) to determine the main production base. The results of this study indicate that West Toili District has the largest harvested area (12,035 hectares), followed by Toili (11,605 hectares) and Moilong (5,038 hectares). Toili is the largest rice-producing district (67,309 tons) with an average productivity of 5.80 tons/ha. Toili, West Toili, Moilong, and Masama are the main rice production bases with LQ values ​​> 1.00, with other sub-districts contributing to lower distribution. Less productive sub-districts need to improve cultivation technology and irrigation networks, thereby providing production facilities. Mapping can be used as a strategic reference for local governments in developing agricultural policies to achieve sustainable food security.